Pengaruh Kinerja Keuangan, Risk Based Capital, dan Faktor Makro Ekonomi Terhadap Harga Saham Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia - Achmad Ramadhoni; Yusdianto Yusdianto; Sutanto Hardisaputera (Syntax Idea, 2022)
Analysts and investors always pay attention to stock price movements from time to time as a reference in investing in financial markets. Many factors affect stock price fluctuations. These factors can be in the form of financial performance factors that refer to the company's financial ratios, such as: increase in assets, decrease in debt, increase in equity, revenue growth, costs, net income, dividends, or it can also be due to macroeconomic factors, for example: balance of payments, unemployment, interest rates, inflation, economic growth or it could be because of the exchange rate. Considering that these factors have different effects on each company which is reflected in its share price, this study was conducted to analyze the effect of several company financial ratios, risk based capital, and macroeconomics on the closing stock price of general insurance companies and losses. on the Indonesia Stock Exchange (IDX) in 2015-2019. There are four insurance companies selected as research samples using non-probability random sampling based on the consideration that the four insurance companies are insurance companies that have the largest total assets in the group of insurance companies that have gone public on the IDX. The research period was carried out for five years, namely from 2015-2019. The data were analyzed using multiple regression analysis (multiple regression analysis) with financial ratios, risk based capital, interest rates, inflation, economic growth and exchange rates as independent variables while the closing stock price of insurance companies as the dependent variable tested at a significance level of = 5 % with the help of SPSS version 25 software. The results showed that the effect of financial ratios, risk based capital, interest rates, inflation, economic growth, and exchange rates on closing stock prices in general insurance companies and losses was relative and varied. Partial test results at PT Asuransi Bintang Tbk only return on assets, return on equity, inflation rate, and exchange rate which have a significant effect on stock prices. At PT Asuransi Dayin Mitra Tbk partially only risk based capital and debt to equity ratio have a significant effect on stock prices. At PT Lippo General Insurance Tbk partially only the inflation rate has a significant effect on stock prices. At PT Panin Insurance Tbk partially only the inflation rate has a significant effect on stock prices. But simultaneously the company's financial ratios, risk based capital, interest rates, inflation, economic growth, and exchange rates have a significant influence on the variance of closing stock prices in the four insurance companies. Based on the results of the study, it also shows that the company's financial ratios, risk based capital, interest rates, inflation, economic growth, and exchange rates have contributed to explain the variance of closing stock prices of each at PT Asuransi Bintang Tbk of R2 = 89.1%, at PT Asuransi Dayin Mitra Tbk at R2 = 95.2%, at PT Lippo General Insurance Tbk at R2 = 83.5%, and at PT Panin Insurance Tbk at R2 = 79.1%. This means that the variance of the insurance company's stock price is quite a lot determined by the company's financial performance, risk based capital, and macroeconomics in this case the interest rate, inflation, economic growth, and exchange rate although the effect varies quite a bit for each company and is only slightly affected. by other factors.